2017
DOI: 10.1002/adfm.201701083
|View full text |Cite
|
Sign up to set email alerts
|

3D Microstructured Carbon Nanotube Electrodes for Trapping and Recording Electrogenic Cells

Abstract: Electrogenic cells such as cardiomyocytes and neurons rely mainly on electrical signals for intercellular communication. Microelectrode array (MEA) devices have been developed to both record and stimulate electrogenic cell. This technology is fuels new insights in the operation of electrogenic cells and the operation of the brain, and is particularly suitable for long-term recording of cell signals under low cell stress conditions. To date, microelectrode arrays are relying on flat or needle shaped electrode s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 53 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…Regardless of the technology, a common goal is to maximize cell–electrode adhesion and electrical coupling in order to achieve high signal quality. Strategies include selective coating of the electrodes using adhesive biomolecules, conductive polymers, or carbon nanomaterials …”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the technology, a common goal is to maximize cell–electrode adhesion and electrical coupling in order to achieve high signal quality. Strategies include selective coating of the electrodes using adhesive biomolecules, conductive polymers, or carbon nanomaterials …”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) are very attractive nanomaterials for biotechnology due to their unique geometric (high aspect ratio, uniform diameter), physical (strength and stiffness of individual nanotubes, electrical and thermal conductivity), and chemical (controllable surface moieties) characteristics. CNTs have been tested in several biotechnology applications, including monitoring the electrical activity of electrogenic cells, , as scaffolds for cell growth and as antimicrobial agents. , Most current studies on the antimicrobial properties of CNTs (Table S1) are performed on CNTs dispersed in suspension, whereby CNT “needles” are hypothesized to act as darts that pierce bacterial cells, however, the physical interaction between bacterial cells in suspension compared to incubation on a nanostructured surface is quite different, as shown by this study. In media, CNTs are proposed to physically pierce the bacterial cells, leading to a loss of cell viability; moreover, chemical functionalization of CNTs by plasma treatment was found to enhance cell-CNT contacts through greater attractive forces between the cell and CNTs. Using CNT suspensions has some significant downsides compared to solid substrata for the testing of antimicrobial activity.…”
mentioning
confidence: 99%
“…8,13 Carbon nanotubes (CNTs) are very attractive nanomaterials for biotechnology due to their unique geometric (high aspect ratio, uniform diameter), physical (strength and stiffness of individual nanotubes, electrical and thermal conductivity), and chemical (controllable surface moieties) characteristics. 14−18 CNTs have been tested in several biotechnology applications, including monitoring the electrical activity of electrogenic cells, 19,20 as scaffolds for cell growth 21 and as antimicrobial agents. 22,23 Most current studies on the antimicrobial properties of CNTs (Table S1) are performed on CNTs dispersed in suspension, whereby CNT "needles" are hypothesized to act as darts that pierce bacterial cells, however, the physical interaction between bacterial cells in suspension compared to incubation on a nanostructured surface is quite different, as shown by this study.…”
mentioning
confidence: 99%
“…Besides, the nanoscale size provides better spatial resolution, making it possible to monitor and regulate the charge transfer of a single cell. Therefore, various low‐dimensional nanomaterials have been considered as substitutes for the conventional electrodes, including metal‐based nanomaterials such as Au nanoparticles, [ 121 ] carbon‐based nanomaterials such as C nanotubes [ 122 ] and graphene, [ 123 ] and semiconductor‐based materials such as Si nanowires, [ 66 , 124 ] gallium phosphide (GaP) nanowires, [ 125 ] and 2D sulfides. [ 126 ] Developing new types of low‐dimensional nanomaterials as electrodes has gained significant attention, and various reviews can be found in this field.…”
Section: Advanced Designs Of Implants With Charge‐transfer Monitoring or Regulating Abilitiesmentioning
confidence: 99%